Experimental and numerical analyses of thermal performance of a thin-film multi-layer insulation for satellite application. (September 2019) - Mesforoush, H.; Pakmanesh, M.R.; Esfandiary, H.; Asghari, S.; Baniasadi, E.
Highlights: The effective emittance of two types of MLI blankets is measured. The effects of thermal conductivity of thin film and shield thickness are analyzed. The thermal model of MLI blankets are developed considering the film thickness. Abstract: Multi-layer insulation (MLI) blankets are one of the main components of satellite thermal control system. The past studies have considered infinite heat transfer coefficient in modeling the MLI shields due to the use of reflective thin films such as aluminized Kapton (Polyimide Film Developed by DuPont Company) or aluminized PET (Polyethylene Terephthalate) in MLI shields. Therefore, equal temperature was considered on two sides of a shield and the effect of thermal resistance has been ignored in the total thermal resistance. In the present study, the effects of thermal conductivity of thin film and shield thickness are analyzed. For this purpose, numerical analyses are performed on three types of blankets that are made of Kapton, PET and null shields. The results indicate that the difference in effective emittance of Kapton and PET blanket is 17% to 2% from the thinnest film to the thickest film, respectively. In order to confirm the numerical results, the effective emittance of two types of MLI blankets made of Kapton and PET films is measured under identical conditions. It is concluded that the Kapton blanket has lower effective emittance than PET.